The Development of Listening Teaching Materials For Indonesian Language For Foreign Speakers (BIPA) Based On Millealab Virtual Reality At The Indonesian Embassy In Paris - Iqbal Ifada; Liliana Muliastuti; Miftahulkhairah Anwar (Dinasti Publisher, 2024)
The current Indonesian Language Program for Foreign Speakers (BIPA) plays a crucial role in advancing Indonesia by increasing the interest of other countries in learning Indonesian culture and language. The scarcity of available listening skill teaching materials for educational purposes poses a challenge to the teaching and learning process of Indonesian culture and language. This research aims to develop teaching materials for listening to Indonesian for Foreign Speakers (BIPA) based on the Millealab Virtual Reality application. The research method employed is Research and Development (R&D) using the Borg and Gall model. Of the ten steps, this study adopts only five: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, and (5) design revision. The research instruments include observation activities, questionnaires, interview guides, and expert validation sheets to obtain the desired data. The teaching materials developed in this study are prototypes of BIPA listening teaching materials based on Millealab Virtual Reality. The research output, a prototype of Millealab Virtual Reality-based BIPA listening teaching materials, has been validated by experts, indicating that the developed Millealab Virtual Reality-based listening teaching materials are feasible for use.